Outcomes of the Supine Anterior-based Muscle-sparing Approach for Primary and Revision Hip Arthroplasty. (February 2022) - Pan, Tommy; Mehta, Anuj; Mason, Mark W.
Abstract : Introduction: Risks and outcomes of total hip arthroplasty (THA) are believed to vary relative to the surgical approach. This study compares the supine anterior-based muscle-sparing (ABMS) approach with its modern-day counterparts. Methods: A retrospective review was done on 550 patients undergoing primary or revision THA from 2016 to 2018. Surgical modalities included direct anterior (DAA), ABMS, posterolateral, and Müller modified Hardinge approaches. Surgical data were collected, and clinical outcomes were measured by the Hip Disability and Osteoarthritis Outcome Score, Modified Harris Hip Score, UCLA, and VR-12 Mental/Physical scores preoperatively and compared clinical outcomes among approaches. Results: A total of 550 patients were included (447 primaries, 103 revisions). The average age was 64 years (231 men, 319 women). Approaches included 79 DAA (14%), 212 ABMS (39%), 180 modified Müller-Hardinge (33%), and 79 posterolateral (14%). The incidence of lateral femoral cutaneous nerve injury was more common with the DAA ( P = 0.008), but no other clinically significant differences were noted among the groups. Conclusion: The results of this study showed no clinically notable differences between the supine ABMS and other approaches. The supine ABMS approach is an acceptable approach in modern day THA when used by an experienced surgeon well-versed in the approach.